Implementation of Good Corporate Governance on Indonesia's State-Owned Enterprises : BUMN Karya WIKA - Fitri Nur Rilah; Sri Trisnaningsih (International Journal of Management Research and Economics, 2025)
The study aims to understand the implementation of Corporate Governance (CG) in one of the State-Owned Enterprises (SOEs) listed on the IDX named WIKA. In 2023, it was reported that there was financial statement manipulation, raising public doubts about the poor CG implementation in the SOE. This study used the Publish or Perish application to select and summarize the literature. The literature reviewed includes annual reports posted on IDX, scientific articles, and relevant books. The result of this study is that WIKA has implemented Good Corporate Governance (GCG) with the TARIF principles and regulations under the legal framework in Indonesia. The principle of transparency is applied with the openness of annual report information at IDX by Financial Services Authority regulations (POJK). Accountability, containing clarity of the functions of business entity organs, refers to the law of limited liability companies (LLCs). Responsibility is applied through mapping implementation approaches and issues considered by various stakeholders. Independence focuses on the core value of AKHLAK for BUMN HR and the use of independent auditors to conduct financial statement audits. Still, from 2020 to 2023, WIKA consecutively used the same public accountant's services. Fairness, prioritizing human rights equality for every worker, shareholder, and stakeholder.